Traffic air pollution and mortality from cardiovascular disease and all causes: a Danish cohort study - Raaschou-Nielsen Ole; Andersen Zorana; Jensen Steen; Ketzel Matthias; Sørensen Mette; Hansen Johnni; Loft Steffen; Tjønneland Anne; Overvad Kim (BMC, 2012)
Abstract Background Traffic air pollution has been linked to cardiovascular mortality, which might be due to co-exposure to road traffic noise. Further, personal and lifestyle characteristics might modify any association. Methods We followed up 52 061 participants in a Danish cohort for mortality in the nationwide Register of Causes of Death, from enrollment in 1993-1997 through 2009, and traced their residential addresses from 1971 onwards in the Central Population Registry. We used dispersion-modelled concentration of nitrogen dioxide (NO2) since 1971 as indicator of traffic air pollution and used Cox regression models to estimate mortality rate ratios (MRRs) with adjustment for potential confounders. Results Mean levels of NO2 at the residence since 1971 were significantly associated with mortality from cardiovascular disease (MRR, 1.26; 95% confidence interval [CI], 1.06-1.51, per doubling of NO2 concentration) and all causes (MRR, 1.13; 95% CI, 1.04-1.23, per doubling of NO2 concentration) after adjustment for potential confounders. For participants who ate < 200 g of fruit and vegetables per day, the MRR was 1.45 (95% CI, 1.13-1.87) for mortality from cardiovascular disease and 1.25 (95% CI, 1.11-1.42) for mortality from all causes. Conclusions Traffic air pollution is associated with mortality from cardiovascular diseases and all causes, after adjustment for traffic noise. The association was strongest for people with a low fruit and vegetable intake.